Molecular regulation after mucosal injury and regeneration in ulcerative colitis - Lie Zheng; Sheng-Lei Duan; Xin-Li Wen; Yan-Cheng Dai (Frontiers in Molecular Biosciences, 2022)
Ulcerative colitis (UC) is a chronic nonspecific inflammatory disease with a complex etiology. Intestinal mucosal injury is an important pathological change in individuals with UC. Leucine-rich repeat-containing G protein-coupled receptor 5 (LGR5+) intestinal stem cells (ISCs) exhibit self-renewal and high differentiation potential and play important roles in the repair of intestinal mucosal injury. Moreover, LGR5+ ISCs are intricately regulated by both the Wnt/β-catenin and Notch signaling pathways, which jointly maintain the function of LGR5+ ISCs. Combination therapy targeting multiple signaling pathways and transplantation of LGR5+ ISCs may lead to the development of new clinical therapies for UC.